DOES TELEVISION PROMOTE DEAGRARIANIZATION? Understanding Rural-Youth Perception Towards the Agricultural-livelihood information on Television - Yogaprasta Adi Nugraha; David Rizar Nugroho (Institut Pertanian Bogor, 2021)
The phenomenon of the high number of rural-youth migration from rural areas need to be studied from the perspective on how the agricultural livelihood is constructed by actors within the village. This research tries to focus on how rural-youth interpret messages on television about agricultural livelihood. Previous studies have explained that there are several things that can cause youth in the village to migrate out of the village. This study aims to (1) identify the characteristics of youth in Ciasmara Village, Pamijahan District, Bogor Regency, (2) Rural-youth Exposure in watching television. (3) Perceptions of rural youth on agricultural information representations on television. This research was conducted in Ciasmara village, Pamijahan District, Bogor Regency from March 2020 to August 2020 using quantitative research methods with a descriptive-comparative approach. 120 youth were selected as research samples. This research found that some of rural-youth in Ciasmara village admitted to having watched agricultural programs on television either on the news or in other programs in the last six months. The types of agricultural information that rural-youth in Ciasmara village have watched are mostly related to cultivation, harvest failure, pest attacks, and low agricultural prices.